Spontaneous fluctuations in neural responses to heartbeats predict visual detection - Park, Hyeong-Dong; Correia, Stéphanie; Ducorps, Antoine; Tallon-Baudry, Catherine (Nature neuroscience, 2014)
Here, using magnetoencephalography, the authors show that in humans, neural events locked to heartbeats before stimulus onset predict the detection of a faint visual grating in the posterior right inferior parietal lobule and ventral anterior cingulate cortex, two regions with multiple functional correlates that belong to the same resting-state network. Spontaneous fluctuations of ongoing neural activity substantially affect sensory and cognitive performance. Because bodily signals are constantly relayed up to the neocortex, neural responses to bodily signals are likely to shape ongoing activity. Here, using magnetoencephalography, we show that in humans, neural events locked to heartbeats before stimulus onset predict the detection of a faint visual grating in the posterior right inferior parietal lobule and the ventral anterior cingulate cortex, two regions that have multiple functional correlates and that belong to the same resting-state network. Neither fluctuations in measured bodily parameters nor overall cortical excitability could account for this finding. Neural events locked to heartbeats therefore shape visual conscious experience, potentially by contributing to the neural maps of the organism that might underlie subjectivity. Beyond conscious vision, our results show that neural events locked to a basic physiological input such as heartbeats underlie behaviorally relevant differential activation in multifunctional cortical areas.